No Man Of God - Wood, Elijah, 1981-; Kirby, Luke, 1978-; Palladino, Aleksa, 1980-; Patrick, Robert, 1937-; Sealey, Amber Rose ([Place of publication not identified] : RLJ Entertainment, Inc, 2021)
In 1980, Ted Bundy was sentenced to death. In the years that followed, he agreed to disclose the details of his crimes, but only to one man.
Keywords: Bundy, Ted; Criminal investigation; Murder -- Investigation; Crime